2019
DOI: 10.1021/acsomega.9b00132
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Water Splitting through the NixSy Self-Grown Superstructures Obtained via a Wet Chemical Sulfurization Process

Abstract: We report water-splitting application of chemically stable self-grown nickel sulfide (Ni x S y ) electrocatalysts of different nanostructures including rods, flakes, buds, petals, etc., synthesized by a hydrothermal method on a three-dimensional Ni foam (NiF) in the presence of different sulfur-ion precursors, e.g., thioacetamide, sodium thiosulfate, thiourea, and sodium sulfide. The S 2– ions are produced after decomposition from res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Here, the amount of oxygen produced matches well with the theoretical values showing nearly 97.55 ± 2.3% of faradic efficiency (Figure S13). From the literature survey, it has been observed that the metal sulfides develop metal oxides, hydroxides, and oxy-hydroxides on their surface during the OER in an alkaline medium, , whereas some reports have claimed the intactness of the sulfide surface even after the long-term stability test. In the present investigation, we observe a partial surface transformation from sulfide to oxide/oxo-hydroxide and sulfate and an excellent electrocatalytic performance similar to other metal chalcogenides and phosphide-based OER electrocatalysts. , Here, these oxidized centers are assumed to provide real catalyst sites for the OER process. , However, VS x is still responsible for maintaining the electronic conductivity among the oxidized surface and the electrode, facilitating fast charge transport that leads to enhanced electrocatalytic performances. , …”
Section: Resultssupporting
confidence: 59%
“…Here, the amount of oxygen produced matches well with the theoretical values showing nearly 97.55 ± 2.3% of faradic efficiency (Figure S13). From the literature survey, it has been observed that the metal sulfides develop metal oxides, hydroxides, and oxy-hydroxides on their surface during the OER in an alkaline medium, , whereas some reports have claimed the intactness of the sulfide surface even after the long-term stability test. In the present investigation, we observe a partial surface transformation from sulfide to oxide/oxo-hydroxide and sulfate and an excellent electrocatalytic performance similar to other metal chalcogenides and phosphide-based OER electrocatalysts. , Here, these oxidized centers are assumed to provide real catalyst sites for the OER process. , However, VS x is still responsible for maintaining the electronic conductivity among the oxidized surface and the electrode, facilitating fast charge transport that leads to enhanced electrocatalytic performances. , …”
Section: Resultssupporting
confidence: 59%
“…Due to the introduction of Ni 3 B, overpotential was reduced from 320 to 290 mV at 10 mA cm −2 and substantial stability, Ni 3 B/rGO nanocomposite prepared by the simple solution method was a capable electrocatalyst for the OER reaction 101 . Our group obtained NiF 2 from Ni‐foam that documented 172 mV overpotential at 10 mA cm −2 curent density which is less than Ni‐foam in the same solution (242 MV) 102 . Additionally, Ni x S y materials prepared with various shapes by a thermal method on a 3D Ni‐foam at various sulfur ion sources were applied for water splitting application where 200 mV of overpotential for OER was mentioned for sodium thiosulfate precursor 103 …”
Section: Advances In Ni‐based Electrocatalystsmentioning
confidence: 98%
“…101 Our group obtained NiF 2 from Ni-foam that documented 172 mV overpotential at 10 mA cm À2 curent density which is less than Nifoam in the same solution (242 MV). 102 Additionally, Ni x S y materials prepared with various shapes by a thermal method on a 3D Ni-foam at various sulfur ion sources were applied for water splitting application where 200 mV of overpotential for OER was mentioned for sodium thiosulfate precursor. 103…”
Section: Nickel Oxides With Comentioning
confidence: 99%
“…They are, however, hindered in many applications because of their high cost and scarcity [107]. Researchers have been undertaking several efforts to produce non-precious metal-based water-splitting catalysts, such as sulphides [108], selenides [109], and oxides [110].…”
Section: Electrode Stabilitymentioning
confidence: 99%